Archaeomagnetic evidence for climate change at Sibudu Cave - Herries, A. I. R. (Southern African Humanities, 2021)
In situ magnetic susceptibility (MS) measurements were undertaken on the north, south and east section walls of the trial trench in Sibudu Cave, KwaZulu-Natal, South Africa. All three sections show similar down-section variations in MS. Laboratory-based mineral magnetic measurements on sub-samples identified two major mineral magnetic zones (MMZB and MMZA). MMZB consists of coarser grained ferrimagnetic minerals and a larger proportion of anti-ferromagnetic haematite from spalling of the sandstone rock shelter during the arid, cold conditions of Oxygen Isotope Stage 4 (OIS 4). MMZA, which incorporates all layers from P1 (~60 ka) to BSV and BSS (~1100 AD), is dominated by fine- to ultra-fine-grained ferrimagnetic minerals (magnetite and maghaemite) that reflect the input of derived soils by aeolian activity. MMZA can be divided into three broad Climatic Zones (CZ3, CZ2 and CZ1) that reflect changes in the concentration of ferrimagnetic minerals during three age clusters. These are ~60 ka in OIS 4 and ~50 ka in OIS 3 and ~1100 AD in OIS 1. Optically stimulated luminescence (OSL) dating of the Middle Stone Age (MSA) sequence suggests hiatuses between the age clusters.